Safety and efficacy of NOAC vs. VKA in patients treated by PCI: a retrospective study of the FRANCE PCI registry - Durand, Eric; Verrez, Thibault; Gillibert, Andre; Levesque, Thomas; Barbe, Thomas; Koning, René; Motreff, Pascal; Eltchaninoff, Hélène; Collet, Jean-Philippe; Rangé, Gregoire (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Dual antithrombotic therapy (DAT) combining oral anticoagulation (OAC), preferentially Non-vitamin K antagonist OAC (NOAC) and single antiplatelet therapy (SAPT) for a period of 6 to 12 months is recommended after percutaneous coronary intervention (PCI) in patients with an indication for OAC.Objective: to compare outcomes between vitamin K antagonist (VKA) and NOAC-treated patients in the nation-wide France PCI registry.Methods: All consecutive patients from the France PCI registry treated by PCI and discharged with OAC between 2014 and 2020 were included and followed one-year. Major bleeding was defined as Bleeding Academic Research Consortium (BARC) classification ≥3 and major adverse cardiac events (MACE) as the composite of all-cause mortality, myocardial infarction (MI), and ischemic stroke. A propensity-score analysis was used.Results: Of the 7,277 eligible participants, 2,432 (33.4%) were discharged on VKA and 4,845 (66.6%) on NOAC. After propensity-score adjustment, one-year major bleeding was less frequent in NOAC versus VKA-treated participants [3.1% vs 5.2%, -2.1% (-3.6 to -0.6%), p=0.005 as well as the rate of MACE [9.2% vs 11.9%, -2.7% (-5.0 to -0.4%), p=0.02]. Oneyear mortality was also significantly decreased in NOAC vs VKA-treated participants [7.4% vs 9.9%, -2.6% (-4.7 to -0.5%), p=0.02]. The area under ROC curves of the anticoagulant treatment propensity score was estimated at 0.93, suggesting potential indication bias Conclusions: NOAC seems to have a better efficacy and safety profile than VKA. However, potential indication bias were found.